PENGARUH METODE DEMONSTRASI PADA MATERI PERUBAHAN WUJUD BENDA TEMA 3 TERHADAP HASIL BELAJAR SISWA KELAS 3 SDN TAMBAKROMO 1 - Rifani Anjar Sari; Prima Rias Wana; Tri Wardati Khusniyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2022)
This study aims to determine the effect of the demonstration method on the material of changing the shape of objects on the learning outcomes of grade 3 students at SDN Tambakromo 1. The research method used in this study was a quantitative method with a quasi-experimental research design. The sampling technique in this study used purposive sampling, the samples in this study were students of class 3A as the control class and class 3B as the experimental class with the number of students in each class as many as 22 students. Data collection techniques in this study using tests. The results of this study indicate that the demonstration learning method has an influence on the learning outcomes of third grade students at SDN Tambakromo 1. This can be proven by the results of the independent sample T-Test using SPSS 25, namely the results of sig. tcount 0.018 < ttable 0.05.